Anti-CD20 antibody as consolidation therapy in a patient with primary plasma cell leukemia after high-dose therapy and autologous stem cell transplantation - Gemmel, Christian; Cremer, Friedrich Walter; Weis, M.; Witzens-Harig, Mathias; Moldenhauer, Gerhard; Koniczek, K.-H.; Imbach, Uta; Ho, Anthony Dick; Moos, Marion; Goldschmidt, Hartmut (Annals of hematology, 2002)
In multiple myeloma (MM), circulating malignant B cells are proposed as the proliferative compartment of the disease. In view of the close relationship between multiple myeloma and primary plasma cell leukemia (PCL), an anti-CD20 antibody treatment might also be considered as consolidation for patients with PCL. A 55-year-old patient diagnosed with PCL achieved complete remission after autologous transplantation. A total of four weekly courses of rituximab (375 mg/m2) were administered. Prior to antibody therapy, CD20+ cells comprised 22.6% of the mononuclear cells in peripheral blood (PB) assessed by flow cytometry and were enriched by magnetic activated cell sorting (MACS). In the enriched CD20+ fraction, 0.093% clonotypic cells were detected using a quantitative polymerase chain reaction (PCR) assay based on limiting dilutions. The proportion of clonotypic cells was 0.034% in PB and 0.032% in bone marrow (BM). Rituximab depleted CD20+ cells completely in PB and BM. Tumor load in PB and BM at day 40 and in PB at day 70 did not change in comparison to prior to therapy (0.037% in PB, 0.026% in BM). At day 90, the tumor load increased to 0.066% in PB. At day 120, the patient relapsed with 0.65% CD38++/CD138+/CD20- plasma cells and furthermore no CD20+ B cells in PB. The expansion of plasma cells was accompanied by an increase in the tumor load in both compartments (PB: 0.65%, BM: 1.8%). The accumulation of plasma cells during disease progression without the reappearance of CD20+ cells did not sustain the role of circulating clonotypic B cells as proliferative compartment in our patient. However, it cannot be excluded that rituximab was not able to eradicate malignant B cells, which subsequently contributed to relapse.